2017
DOI: 10.1094/cchem-09-16-0243-r
|View full text |Cite
|
Sign up to set email alerts
|

Volatile Organic Compounds of Whole‐Grain Soft Winter Wheat

Abstract: Cereal Chem. 94(3):594-601The aroma from volatile organic compounds (VOC) is an indicator of grain soundness and also an important quality attribute of grain foods. To identify the inherent VOC of wheat grain unaffected by fungal infestation and other extrinsic factors, grains of nine soft wheat varieties were collected at various days postanthesis (DPA) and analyzed for VOC. Ten VOC were detected in all nine varieties at all DPA. 3-Methyl-1-butanol, 2-methyl-1-butanol, 1-pentanol, hexanal, and 1-hexanol were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…In the raw wheat bran, high concentration of 1‐hexanol was detected (Table ), which is in consistent to the literature that 1‐hexanol is the main alcohol in wheat (Ji et al ., ). This alcohol compound has a green and herbal aroma (Table ).…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…In the raw wheat bran, high concentration of 1‐hexanol was detected (Table ), which is in consistent to the literature that 1‐hexanol is the main alcohol in wheat (Ji et al ., ). This alcohol compound has a green and herbal aroma (Table ).…”
Section: Resultsmentioning
confidence: 97%
“…Amongst all esters, methyl hexanoate was the most abundant. 2‐Pentyl‐furan was detected in raw wheat bran, which was also reported in whole wheat with a fruity and green aroma (Ji et al ., ). It was reported that whole wheat flour had a significantly higher level of 2‐pentyl furan compared to the refined wheat flour (Moskowitz et al ., ), indicating it mainly existed in the bran.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…The result of uncontrolled growing of fungi often is a colour shift to a green–yellowish hue with higher lightness and an approxoimately 1000‐fold increase in colony‐forming units per seed mass . It is also known from other raw materials or food products that fungi result in a change of the volatile profile . A correlation between fungi settlement and changes of the volatile profile of rapeseed or the resulting rapeseed oil has yet not been carried out.…”
Section: Introductionmentioning
confidence: 99%